Correlation between surface air temperature and lightning events in Colombia - Fernando Augusto Díaz-Ortiz; Francisco José Román-Campos (Revista Facultad de Ingeniería Universidad de Antioquia)
This paper presents findings on the correlation between surface air temperature and lightning activity in Colombia. The air temperature data spans several decades, while the lightning data covers 17 years. The temperature records come from nine cities, and the lightning data covers about 50% of the territory. Despite differences in sampling rates and dataset sizes, the findings show a positive correlation between surface air temperature and lightning activity, suggesting a possible relationship between warmer conditions and increased lightning activity.